Mieux comprendre le rôle de THAT à la suite d’un verbe de dire riche - Brigitte BONTHOUX-PHILIPPE (E-REA)
This article explores the impact of the subordinating conjunction THAT on the meaning of an utterance whose syntactic pattern is as follows: subject + non neutral saying verb + clause. First, we will analyze the different aspects of Reported Indirect Speech to understand how the conjunction can help to convey this meaning, its absence making it sometimes impossible to do so. We will then seek to determine when the conjunction is more or less compulsory in relation with the meaning of the introducing verb. Finally, it will be shown that the absence of conjunction does not necessarily produce agrammatical utterances, even when a semantically rich verb is found in the first clause. Indeed, the meaning of the message may just differ, leaving the idea of Reported Speech behind, as well as the kind of relationship between the two parts of the sentence which evolves from a hypotactic relationship to a paratactic one.